Synthesis, Characterization, and Antioxidant Screening of Some New Azo Compounds Containing Pyrazole Moiety from Metoclopramide Drug - Ibrahim, Youssef Mohsen; Khalaf, Mona Ismail (Iraqi Journal of Science, 2023)
In this work, some new pyrazole derivatives were prepared through the reaction of the diazonium salt of metoclopramide with acetylacetone to give 5-chloro-N-(2-(diethylamino)ethyl)-4-((2,4-dioxopentan-3-yl) diazenyl)-2-methoxybenzamide (1) in 80% yield. Compound 1 was then reacted with some hydrazine derivatives to afford the corresponding pyrazole derivatives in 75-93% yields. Some new azo compounds (6-10) were also prepared in 77-95% yields by treatment of the diazonium salt of metoclopramide with some phenol and aniline derivatives. The prepared compounds were characterized using FT-IR and 1H NMR spectroscopy. Some of these compounds were then tested to see how well they worked as antioxidants.